2017
DOI: 10.7554/elife.21884
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule FRET unveils induced-fit mechanism for substrate selectivity in flap endonuclease 1

Abstract: Human flap endonuclease 1 (FEN1) and related structure-specific 5’nucleases precisely identify and incise aberrant DNA structures during replication, repair and recombination to avoid genomic instability. Yet, it is unclear how the 5’nuclease mechanisms of DNA distortion and protein ordering robustly mediate efficient and accurate substrate recognition and catalytic selectivity. Here, single-molecule sub-millisecond and millisecond analyses of FEN1 reveal a protein-DNA induced-fit mechanism that efficiently ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
126
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(142 citation statements)
references
References 53 publications
16
126
0
Order By: Relevance
“…5d). However, handing off a bent DNA is not a must for FEN1 activity since FEN1 can actively bend the nick junction in diffusion-limited kinetics 54,55 . Nick translation occurs at rates that are 10-fold faster than nick DNA product release by FEN1 16,[55][56][57] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5d). However, handing off a bent DNA is not a must for FEN1 activity since FEN1 can actively bend the nick junction in diffusion-limited kinetics 54,55 . Nick translation occurs at rates that are 10-fold faster than nick DNA product release by FEN1 16,[55][56][57] .…”
Section: Resultsmentioning
confidence: 99%
“…A 6× His-tag was introduced at the C-terminus of RPA1 subunit by PCR. The catalytically inactive FEN1-D181A was constructed as described previously 54 . Briefly, the gene sequence encoding WT human FEN1 was cloned via Gibson assembly into a pE-SUMO-pro expression vector (Lifesensors).…”
Section: Methodsmentioning
confidence: 99%
“…At the systems level, we see the importance of maintaining the B-DNA double helix structure, as potential non-B-DNA structures (PONDS) occur at high frequency in cancer as translocations and deletion break points (230). Furthermore, at RFs where the double helix is opened for processing, precise control of DNA ends is needed to avoid not only mutations but also template switching and large repeat expansions (231, 232). These and other data provide compelling support for the notion that DNA structures at forks, ends, and breaks are intrinsic risk factors that complexes such as MRN are under strong evolutionary pressure to tightly control.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…We observed that DNA repair and replication enzymes typically sculpt their DNA substrates, as we found for nucleotide flipping by DNA repair glycosylases (Guan et al, 1998; Slupphaug et al, 1996; Thayer, Ahern, Xing, Cunningham, & Tainer, 1995), AP endonucleases (Tsutakawa et al, 2013), and endonuclease V (Dalhus et al, 2009), as well as for the flap exo- and endonuclease FEN1 (Rashid et al, 2017; Tsutakawa et al, 2017). Thus, part of our strategy to obtain specificity is to retain DNA binding but to block protein-mediated DNA conformational changes needed to position the substrate complex for catalysis.…”
Section: Methods For Avatar Inhibitors Targeting Allosterymentioning
confidence: 58%